SUPERVISION AS MODEL OF PERSONAL AND PROFESSIONAL DEVELOPMENT OF THE SOCIAL WORKERS - Dimitrijoska, Suncica (Ревија за социјална политика/Journal of Social Policy, 2015)
If we take in consideration the complex social problems conditioned by traditional political, economic and social relations in our society in the immediate work with people, there is an evident need for competent professionals, social workers. They should respond to the requests and needs of the current social developments that cannot be treated as traditional, bureaucratic actions in the social work. The social workers are required to follow the complex changes in the society and in the same time to fulfill their function of unchangingness in the social system. The actual context of reforms in the system for social protection in the Republic of Macedonia, and the introduction of numerous innovations and standards in the structural and functional aspects require development of models for intervention. Changes are needed to meet such expectations of the experts, in terms of development of practice based on theory and scientific facts. The contemporary social work requires development and directing competencies, skills, opinions and resolving problems, team work and cooperation focused on the assistance provider. The need for supervision is evident in all systems that work in the area of provision of support to people and development of their potentials, activation and using knowledge, and application of skills in practice. The integrative-developmental supervision is a model which improves professional competencies, creates job satisfaction, prevents professional burnout syndrome and enhances professional efficacy through the process of integration of theory and practice.